High expression of Polycomb group protein EZH2 predicts poor survival in salivary gland adenoid cystic carcinoma. Issue 6 (6th March 2008) - Vékony, H; Raaphorst, F M; Otte, A P; van Lohuizen, M; Leemans, C R; van der Waal, I; Bloemena, E
Abstract : Background: The prognosis of adenoid cystic carcinoma (ACC), a malignant salivary gland tumour, depends on clinicopathological parameters. To decipher the biological behaviour of ACC, and to identify patients at risk of developing metastases, additional markers are needed. Methods: Expression of the cell cycle proteins p53, cyclin D1, p16 INK4a, E2F1 and Ki-67, together with the Polycomb group (PcG) proteins BMI-1, MEL-18, EZH2 and EED was investigated immunohistochemically 21 formalin-fixed, paraffin-embedded primary ACCs in relation to tumour characteristics. Results: ACC revealed significantly increased expression of the cell cycle proteins compared to normal salivary tissue (n = 17). Members of the two PcG complexes displayed mutually exclusive expression in normal salivary gland tissue, with BMI-1 and MEL-18 being abundantly present. In ACC, this expression pattern was disturbed, with EZH2 and EED showing significantly increased expression levels. In univariate analysis, presence of recurrence, poor differentiation and high EZH2 levels (>25% immunopositivity) significantly correlated with unfavourable outcome. ACCs with high proliferative rate (>25% Ki-67 immunopositivity) significantly correlated with high levels of EZH2 and p16. Only the development of recurrence was an independent prognostic factor of survival in multivariate analysis. Conclusions: Expression of PcG complexes and of essential cell cycle proteins is highly deregulated in ACC. Also, EZH2 expression has prognostic relevance in this malignancy.